Multisensor biometric evidence fusion of face and palmprint for person authentication using Particle Swarm Optimisation (PSO). (16th December 2009) - Raghavendra, R.; Rao, Ashok; Hemantha Kumar, G.
This paper presents a novel biometric sensor fusion technique for face and palmprint images using Particle Swarm Optimisation (PSO). The proposed method can be visualised in the following steps: we first decompose the face and palmprint image obtained from different sensors using wavelet transformation and then, we employ PSO to select most informative wavelet coefficients from face and palmprint to produce a new fused image. We then employed Kernel Direct Discriminant Analysis (KDDA) for feature extraction and the decision about accept/reject is carried out using Nearest Neighbour Classifier (NNC). Extensive experiments carried out on a virtual multimodal biometric database of 250 users indicate the efficacy of the proposed method.